A catchment‐scale perspective of plastic pollution - Windsor, Fredric M. (Glob Chang Biol, 2019)
Plastic pollution is distributed across the globe, but compared with marine environments, there is only rudimentary understanding of the distribution and effects of plastics in other ecosystems. Here, we review the transport and effects of plastics across terrestrial, freshwater and marine environments. We focus on hydrological catchments as well‐defined landscape units that provide an integrating scale at which plastic pollution can be investigated and managed. Diverse processes are responsible for the observed ubiquity of plastic pollution, but sources, fluxes and sinks in river catchments are poorly quantified. Early indications are that rivers are hotspots of plastic pollution, supporting some of the highest recorded concentrations. River systems are also likely pivotal conduits for plastic transport among the terrestrial, floodplain, riparian, benthic and transitional ecosystems with which they connect. Although ecological effects of micro‐ and nanoplastics might arise through a variety of physical and chemical mechanisms, consensus and understanding of their nature, severity and scale are restricted. Furthermore, while individual‐level effects are often graphically represented in public media, knowledge of the extent and severity of the impacts of plastic at population, community and ecosystem levels is limited. Given the potential social, ecological and economic consequences, we call for more comprehensive investigations of plastic pollution in ecosystems to guide effective management action and risk assessment. This is reliant on (a) expanding research to quantify sources, sinks, fluxes and fates of plastics in catchments and transitional waters both independently as a major transport routes to marine ecosystems, (b) improving environmentally relevant dose–response relationships for different organisms and effect pathways, (c) scaling up from studies on individual organisms to populations and ecosystems, where individual effects are shown to cause harm and; (d) improving biomonitoring through developing ecologically relevant metrics based on contemporary plastic research.